The Use of Cartoon Film to Teach Listening Narrative Texts to The Eighth Graders of SMPN 1 Menganti (RETAIN, 2018)
Abstract As one of the language skills, listening is the basic skill in learning English a foreign language (EFL). Listening is a very important skill and the fundamental of language as stated by Brown (1980:43) that a small child listens and speaks and no one would dream of making him read or write. In other words, the natural order for the first and second language learning is listening, speaking, reading, and writing. Animation clips could make moving pictures and sound as well that chosen. They also would be more interesting than just listen an audio which only provides sound. Same as the report, teacher can use media like cassettes, tape recorder or MP3 player. Clark (2000; Rule & Ague, 2005) stated that focus of language materials is limited by number of circumstantial studies it is Difference with news, the pedagogical value of cartoons as reliable. In a circumstantial study conducted by Clark (2000), cartoons can involve the attention of the learners and present information in a pleasant atmosphere. Besides, encourage thinking processes and discussion skills is potential that cartoons have (Clark, 2000). Besides, encourage thinking processes and discussion skills is potential that cartoons have (Clark, 2000). The researcher chooses short cartoon films as a media to teach listening narrative because he believes that cartoon could increase student’s motivation and attention to the material that will be given by the teacher. In his experience when he was doing practice teaching, he found that listening which audio sometimes could make them bored. The nice cartoons and films could engage student attention and seem to motivate the learners and good story lines makes them easy to learn the language input better and have a good significant effect to the language development. Kata Kunci: : Listening, Short cartoon film, Narrative text. Abstrak Sebagai salah satu skill di dalam bahasa, listening adalah skli dasar dalam mempelajari Inggris sebagai bahasa asing (EFL). Listening adalah skill yang sangat penting dan menjadi dasar dari bahasa seperti yang di ungkapkan oleh Brown (1980:43) seorang anak kecil mendengar dan berbicara tidak ada seorang pun yang berfikir menyuruhnya membaca dan menulis. Dengan kata lain, Tatanan alami untuk pembelajaran bahasa pertama dan kedua adalah mendengarkan, berbicara, membaca, dan menulis Klip animasi dipilih karena mereka memberikan gambar dan bisa bergerak. Itu juga lebih menarik daripada hanya mendengar suara saja. Sejalan dengan pernyataan, guru dapat menggunakan media seperti kaset CD, tape recorder, MP3, dll. Tidak seperti berita, nilai pedagogis kartun sebagai bahan bahasa asli telah menjadi fokus sejumlah kecil studi anekdot (Clark, 2000; Doring, 2002; Rule & Ague, 2005). Dalam sebuah studi anekdot yang dilakukan oleh Clark (2000), disoroti bahwa kartun dapat menarik perhatian pelajar dan menyajikan informasi dalam suasana yang tidak mengancam. Selain itu, kartun memiliki potensi untuk mendorong proses berpikir dan keterampilan diskusi (Clark, 2000). Studi lain dilakukan oleh Doring (2002) yang memusatkan perhatian pada efek paparan kartun pada pembelajaran bahasa. Peneliti menggunakan film kartun pendek sebagai media mengajar listening pada naratif teks karena dia percaya film kartun dapat meningkatkan motivasi dan perhatian pada pembelajaran yang dilakukan oleh guru. Pada pengalamnya menggunakan rekorder, dia menyadari bahawa listening yang hanya menggunakan audio, membuat siswa cepat bosan . film kartun dengan alur cerita yang bagus membuat siswa tertarik untuk mendengarkan, dan pembelajar menyerap bahasa lebih baik dan lebih memberi efek signifikan pada perkembangan bahasa. Keywords: : Mendengarkan, film kartun pendek, teks narasi..